Bathyeurystomina, a new genus of freeliving marine nematodes (Enchelidiidae) from the Rockal Trough - Lambshead, P. J. D.; Platt, H. M. (Cahiers de Biologie Marine, 1979)
Locality: Rockall trough, Antarctica; Cabinet:
NeMys doc_id: 7203 from NeMys